Comportamento mecânico e influência da argamassa no modo de ruptura da alvenaria estrutural - Lübeck, André (2016)
The literature indicates that mortar strength has little influence on concrete masonry strength, suggesting that the fresh state properties of the mortar are more relevant than the properties of the hardened mortar, and this point of view is reflected on standards and codes. However, the failure mode of the masonry can be dramatically influenced by the properties of the hardened bedding mortar especially when using a mortar with low compressive strength. In such case, mortar crushing can be the masonry failure mode. This study evaluated the influence of bedding mortar on the failure modes of axially loaded masonry through three distinct approaches. The first approach was a visual analysis that used pictures from a high-definition camera to determine the rupture sequence of masonry prisms. The analysis used pictures from tests of four different prism assemblages. The prisms were two and three blocks high with stack-bond and running-bond configurations and constructed with three types of blocks: concrete blocks and hollow and solid walls ceramic blocks. Two mortar types with different strengths were used to assemble the prisms. The visual analysis indicated that mortar crushing happens and completely changes the masonry failure mode. The second approach evaluated the stress-strain behavior of small thickness axially loaded mortar samples with the objective of capturing changes in the mechanical properties of the mortar. The properties of interest were the Poisson’s ratio, volumetric strain, and strain increments. The evaluation demonstrated that crack propagation near failure results in changes on the mechanical properties of the mortar and that those changes can be used as a measure of the degradation of the mortar. The third approach was the development of a finite element model to represent the axially loaded mortar samples. The model used a phased analysis, which allowed the elastic modulus and Poisson’s ratio of the material to be changed during the loading sequence. The nonlinear model was able to capture the strain changes on the confined mortar.